Aktualisasi Dimensi Kewargaan Penuh (Full Citizenship) Dalam Gerakan Perlawanan Nelayan Terhadap Reklamasi Teluk Jakarta Tahun 2016-2020 - Alamsyah, Syauyiid; Wahyuningroem, Sri Lestari (Magister Ilmu Politik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2025)
This research explains the analysis of citizenship politics in Indonesia, which experiences problems of injustice through a case study of the fishermen's resistance movement in Jakarta. Citizenship politics is the perspective used to explain the efforts of citizens in order to achieve full citizenship through social movements. The social movement of the fishermen's resistance group is a practice of actualizing civic politics to fight for equality of citizenship rights. Conflicts between citizens and the state occur because state policies tend to marginalize citizens socially, politically and economically. The methodology in this research uses an explanatory qualitative approach, as a post-positivism approach that explains specifically and in-depth the problem of civic politics through the fishermen's resistance movement against the Gulf reclamation. This case study shows that a policy can be created without the role of participation and equality. Data collection techniques in this research are interviews and focus group discussions (FGDs). The findings of this research reveal that civic politics is weakened because the social, political and cultural rights of citizens are not fulfilled. The weakening of civic politics shows that in addition to the efforts of the state to weaken it, the citizens themselves are also still weak. It is necessary to strengthen the civic politics of the citizens themselves through civic transformation.